2018
DOI: 10.1111/andr.12531
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation media differentially affect sperm motility, morphology and DNA integrity

Abstract: This study indicates that the recovery rate of competent spermatozoa, after cryopreservation, is still critical in infertile men. Therefore, frozen semen sample should be used only when necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 57 publications
(90 reference statements)
5
50
0
Order By: Relevance
“…As expected, post‐thawed sperm parameters were significantly decreased compared to the pre‐freeze state. Our results confirmed Raad et al () findings who demonstrated that frozen‐thawed spermatozoa exhibited a decline in sperm quality in normozoospermic samples compared to fresh semen (Raad et al, ). Similarly, Zribi et al () reporting on sperm motility, viability and DNA integrity before and after cryopreservation with supplementation of antioxidants in the freezing medium, showed that the motility and viability of spermatozoa were reduced after the freezing–thawing process.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, post‐thawed sperm parameters were significantly decreased compared to the pre‐freeze state. Our results confirmed Raad et al () findings who demonstrated that frozen‐thawed spermatozoa exhibited a decline in sperm quality in normozoospermic samples compared to fresh semen (Raad et al, ). Similarly, Zribi et al () reporting on sperm motility, viability and DNA integrity before and after cryopreservation with supplementation of antioxidants in the freezing medium, showed that the motility and viability of spermatozoa were reduced after the freezing–thawing process.…”
Section: Discussionsupporting
confidence: 92%
“…Although sperm cells have the ability to adapt to osmotic changes [ 79 ], freezing medium does not fully protect them from the osmotic stress happening during freezing and thawing that leads to an increase in ROS production, apoptosis-like changes, DNA damage, and an increase in tail defects [ 80 , 81 , 82 ]. Therefore, we hypothesized that the addition of cAMSC-CM to the freezing medium would increase sperm tolerance to osmotic changes, oxidative defence, and help protect their ultra-structure, because it contains proteins with anti-oxidant, regenerative, and anti-apoptotic effects ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cryopreservation process leads to an increase in sperm tail abnormalities [ 80 , 84 ], altered acrosome and plasma membrane integrity [ 85 ], and a decrease in the mitochondrial activity [ 4 , 82 ] and motility [ 80 , 82 ]. In our study, we found that the percentage of coiled tail sperm was the same in both groups, but the percentage of sperm with a bent tail was significantly reduced in the 10% CM-treated group in comparison with the control group ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory conditions (i.e., prolonged incubation, centrifugation, cryopreservation and use of different media) can significantly impact SDF by increasing OSmediated DNA damage [228][229][230][231]. Conventional (swimup, DGC) and advanced techniques can select sperm with low levels of SDF [232][233][234][235][236] (Table 3).…”
Section: Sperm Processing and Preparationmentioning
confidence: 99%